2008
DOI: 10.1021/jp710259v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Electromagnetic Functionalized Barium Ferrite Nanoparticles Embedded in Polypyrrole

Abstract: With flaky BaFe12O19 nanoparticles (BF NPs, 10-20 nm in thickness) as polymerization seeds, electromagnetic functionalized and microstructured quasi-spherical PPY/BF (PPY: polypyrrole) organic-inorganic composites were prepared by a conventional in situ chemical oxidative polymerization. X-ray diffraction and Fourier transform infrared analyses interpreted that there was no obvious chemical interaction between BF NPs and PPY in the composites but that BF NPs only served as the nucleation sites for the polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…[5,19] The bands at about 1 047 cm À1 (the C-H and N-H in-plane deformation vibration) and between 940 and 925 cm À1 (the stretching vibration of doped PPy) became stronger with increasing PPy component. [20] In contrast, the bands between 800-790 cm À1 (the C-H out-of-plane ring deformation vibration), at about 1 490 cm À1 (the C --C stretching modes of the benzenoid ring) and at about 1 295 cm À1 (the C-N stretching modes of the leucoemeraldine) became weaker with increasing the dosage of Py monomer during the polymerization process. Surprisingly, the C-H in-plane bending mode of permigraniline at 1 140 cm À1 was discovered only for the nanofibers from [An:Py] ¼ 9:1, 3:1 and 1:1, [21,22] and completely disappeared in the other two PANI-PPy nanofibers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5,19] The bands at about 1 047 cm À1 (the C-H and N-H in-plane deformation vibration) and between 940 and 925 cm À1 (the stretching vibration of doped PPy) became stronger with increasing PPy component. [20] In contrast, the bands between 800-790 cm À1 (the C-H out-of-plane ring deformation vibration), at about 1 490 cm À1 (the C --C stretching modes of the benzenoid ring) and at about 1 295 cm À1 (the C-N stretching modes of the leucoemeraldine) became weaker with increasing the dosage of Py monomer during the polymerization process. Surprisingly, the C-H in-plane bending mode of permigraniline at 1 140 cm À1 was discovered only for the nanofibers from [An:Py] ¼ 9:1, 3:1 and 1:1, [21,22] and completely disappeared in the other two PANI-PPy nanofibers.…”
mentioning
confidence: 99%
“…) are considerably lower than the homopolymers, [17,20] and a first order exponential decay as a function of PPy content was displayed (see Supporting Information). It was recognized that metal ions having a reduction potential higher than that of the PANI can be reduced to form metal elements.…”
mentioning
confidence: 99%
“…27 Xu et al achieved a maximum reflection loss of À11.8 dB at 11.6 GHz by 13.5 wt% barium ferrite nanoparticles loaded polypyrrole composite with a thickness of 2 mm. 28 Herein, we report the successful preparation of BaFe 12 O 19 decorated RGO nanocomposite through the high energy ball milling method. The microwave shielding and dielectric properties of the nanocomposite were studied in the 12.4-18 GHz frequency range and it was observed that the incorporation of BaFe 12 O 19 significantly contributes towards the enhanced microwave absorbing performance, which is due to its high magnetic losses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few articles on the functional organic-inorganic composites have been published. P Xu et al [8] prepared polypyrrole functionalized BaFe 12 O 19 nanoparticles. As compared to pure ferrite, the functional composites showed distinct increases in electrical conductivities and enhancement of reflection loss at 2-18 GHz.…”
Section: Introductionmentioning
confidence: 99%